Walking a Fine Line: How Norwegian Public Library Staff Navigate Activism and Neutrality in Their Settings - Phinney, Jackie (Evidence Based Library and Information Practice, 2025)
A Review of: Solum, E. E. B. D. (2025). Negotiating neutrality and activism in Norwegian public libraries: the case of environmental sustainability. Journal of Documentation, 81(1), 107-124. https://doi.org/10.1108/JD-04-2024-0082 Objective – To explore the idea of public library staff’s environmental activism in Norway and determine how they view library neutrality when considering the United Nations (UN) Sustainable Development Goals (SDGs). Design – Qualitative study design using semi-structured interviews. Setting – Four public libraries in Norway: The Northern and central-Eastern regions (2), and Oslo (2). Subjects – 30 Librarians and non-librarians from the Norwegian public library sector, with a range of 1-38 years of employment in the library system. Methods – The researcher recruited participants from the chosen library locations, conducted semi-structured interviews with participants, and analyzed data by library location using deductive-inductive methods. They also conducted field visits to each library and reviewed internal documents. Main Results – The data revealed that the library’s support of the SDGs is context-dependant, and that negotiating between advocacy and neutrality may occur through library initiatives that are not outwardly political. Interview participants described their thoughts surrounding library neutrality during event-planning, with some feeling that demonstrating a stance on climate issues could reignite negative biases about public libraries. Other participants felt that if events are hosted, skeptical voices should be welcomed to offer balanced discussion. The data suggested that neutrality and activism are impacted by professional competencies, as librarians who are hired to support sustainability initiatives may lead efforts that are later adopted by other professionals and organizations. Conclusion – Norwegian public library staff are aware that environmental activism is important and are determining how best to address the UN’s SDGs while also welcoming patrons with various views.